Pengaruh penerapan model Problem Based Learning (PBL) pada materi pemanasan global terhadap kompetensi berfikir kritis siswa - Aniza; Khusnah, Laila (Universitas Tangerang Raya, 2024)
This research is motivated by students' difficulties in understanding the material in depth so that students tend to be passive when learning and this affects their learning outcomes. The PBL model is an appropriate learning model for students to develop their knowledge and be actively involved in learning. The aim of this research is to determine the effect of applying the PBL model on students' critical thinking competence in class VII global warming material at MTsN 2 Jember. This research is a quasi-experimental research with a nonequivalent posttest-only control group design. Research data was obtained using an observation sheet instrument to measure critical thinking competence. The research results have been tested using the independent samples t-test statistical test, obtaining a significance value of 0.000 for critical thinking competence, so it was decided that H0 was rejected and Ha was accepted. It can be concluded that there is an influence of the application of the PBL model on students' critical thinking competence in global warming material in class VII MTsN 2 Jember.